ANALYSIS OF THE ANTIOXIDANT PROPERTY, CYTOTOXICITY AND ANTI-TUMOUR EFFICIENCY OF BAUHINIA PHOENICEA. - Baby, Alby Alphons; Raphael K, Regi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Bauhinia phoenicea Wight and Arn. is a medicinal plant endemic to Southern Western Ghats. In the traditional systems of medicine, it is using against various ailments including some oxidative disorders. Detailed studies on the pharmacological activities of this plant are not yet reported. Hence, this paper aimed to prove the efficacy of this plant as a natural antioxidant source. Methods: The sequential extracts of the dried leaf powder were assayed for an antioxidant property using 2,2 diphenyl 1-picrylhydrazyl free radical scavenging assay, in vitro cytotoxicity of the extracts was screened using Trypan blue exclusion method. The antitumor activity of the selected fractions was studied using ascites tumor affected mice and noted the percentage of increase in lifespan. Results: The free radical scavenging activity of all extracts was increasing with increasing concentration of the drug, the least IC50 value was showed by ethanol fraction (41 Î¼g/ml). The plant drug was not toxic to the normal cells and was highly toxic to tumor cell lines. Maximum in vitro cytotoxicity was observed in chloroform fraction (98% cell death at 100 mg/ml) and the least IC50 value was exhibited by the aqueous fraction (34 mg/ml). Both the aqueous and chloroform fractions increased the lifespan of ascites tumor bearing mice, aqueous fraction in 100 mg/ml concentration shows 71.9% increase in lifespan which is near to the result showed by the commercial anticancer drug cyclophosphamide (72.5%). Conclusion: According to our results, it is concluded that leaf of B. phoenicea has significant antioxidant, cytotoxic, and antitumor properties supporting the folk medicinal use of this species. The further procedures of identification of pharmacological active principles are in progress.